Organic Semiconductor and Transistor Electrical Characteristic Based on Carbon Nanotubes - Kianoosh Safari; Ali Rafiee; Hamidreza Dalili Oskouei (Institute of Advanced Engineering and Science, 2016)
We show that the performance of pentacene transistors can be significantly improved by maximizing the interfacial area at single walled carbon nanotube (SWCNT)/pentacene. The interfacial areas are varied by anchoring short SWCNTs of different densities (0-30/μm) to the Pd electrodes. The mobility average is increased three, six and nine times for low, medium and high SWCNT densities, respectively, compared to the devices with zero SWCNT. The current on-off ratio and on-current are increased up to 40 times and 20 times with increasing the SWCNT density. We explain the improved device performance using reduced barrier height of SWCNT/pentacene interface.